Novel Hypoxanthine Guanine Phosphoribosyltransferase Gene Mutations in Saudi Arabian Hyperuricemia Patients - Alanazi, Mohammed (Hindawi Publishing Corporation, 2014)
Over the past decade, a steady increase in the incidence of HPRT-related hyperuricemia (HRH) has been observed in Saudi Arabia. We examined all the nine exons of HPRT gene for mutations in ten biochemically confirmed hyperuricemia patients, including one female and three normal controls. In all, we identified 13 novel mutations in Saudi Arabian HPRT-related hyperuricemia patients manifesting different levels of uric acid. The Lys103Met alteration was highly recurrent and was observed in 50% of the cases, while Ala160Thr and Lys158Asn substitutions were found in two patients. Moreover, in 70% of the patients ≥2 mutations were detected concurrently in the HPRT gene. Interestingly, one of the patients that harbored Lys103Met substitution along with two frameshift mutations at codons 85 and 160 resulting in shortened protein demonstrated unusually high serum uric acid level of 738 μmol/L. Two of the seven point mutations that resulted in amino acid change (Lys103Met and Val160Gly) were predicted to be damaging by SIFT and Polyphen and were further analyzed for their protein stability and function by molecular dynamics simulation. The identified novel mutations in the HPRT gene may prove useful in the prenatal diagnosis and genetic counseling.